Primary dyscalculia after a medial frontal lesion of the left hemisphere. Issue 3 (March 1993) - Lucchelli, F; De Renzi, E
Abstract : A patient had an infarct in the territory of the left anterior cerebral artery, which destroyed the medial cortex of the frontal lobe, and presented with a picture of primary dyscalculia. Lexical and syntactic processing of verbal and arabic numbers and comprehension of operation symbols were intact, but retrieval of basic, over-learned facts was mildly impaired and execution of calculation procedures was more severely impaired. As the same type of procedure could be passed or sometimes failed it suggests a deficit of activation of the appropriate procedures. The location of the lesion was unusual and suggested participation of medial frontal areas in calculation processes.